Implementation Community Base Tourism (CBT) Identification - Brantas Brantas (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
Community-based tourism aims to develop tourism potential by actively involving local communities. Tourism villages are the main focus in the development of community-based Tourism. Indonesia has a rich cultural heritage and natural environment that can provide authentic experiences to tourists. The research identified the potential of developing a tourism village with community participation. The research endeavors to uncover patterns of success and challenges across cases, shedding light on best practices and potential pitfalls in implementing community-based tourism initiatives. The Regional Regulation of Bandung Regency Number 4 of 2019 concerning the 2018-2025 Regional Tourism Development Master Plan, Desa Lamajang is included in the Regional Tourism Development Area (KPPD) for Wisata Petualangan Alam Lamajang, whose tourism product development theme is tourism village areas and special interests, as well as development targets. In the form of applying the concept of developing special interest tourist areas and tourist villages through community empowerment while maintaining the quality of the ecological environment.Furthermore, Desa Lamajang is relevant for implementing community-based tourism because that community participation in increasing tourist interest, especially for Pilot Tourism Village, can support the government's plans for sustainable tourism.